Avaliação de cell-free DNA (cfdna) como preditor de gravidade em pacientes sépticos do Hospital Universitário Cassiano Antônio de Moraes (Hucam) - Claudio, Livia Maria de Araujo Maia (2019)
Introduction: Sepsis is a systemic response of the body to a microbial infection. It is estimated that 19 million cases worldwide occur each year with high case fatality rates and is considered a serious public health problem. Diagnosing sepsis remains a major challenge for healthcare professionals, and so far, there is no gold standard for diagnosing sepsis. New biomarkers, such as cfDNA, have been studied in sepsis to improve diagnosis and allow early therapeutic intervention. Objective: To investigate the value of cfDNA as a predictor of severity in septic patients and its association with organ dysfunction score. Methods: 124 patients who had the sepsis protocol started were divided into infection (n=37) and sepsis/septic shock (n=87). Clinical and epidemiological data were obtained from medical records. Blood samples were collected at diagnosis and cfDNA concentrations were measured by the direct fluorescence technique. Results were presented in ng/ml. Results: cfDNA concentrations were higher according to disease severity. Higher cfDNA values (p